PENGARUH WORK-LIFE BALANCE, STRES KERJA, DAN BEBAN KERJA TERHADAP TURNOVER INTENTION MELALUI BURNOUT SEBAGAI VARIABEL INTERVENING PADA KARYAWAN GEN Z DESA BATTAL - Ilmiya Ilmiya; Minullah Minullah; Ediyanto Ediyanto (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of Work-Life Balance, Job Stress, and Workload on Turnover Intention through Burnout as an intervening variable among Generation Z employees in Battal Village. This research employed a quantitative method with a non-probability sampling technique using purposive sampling. The total sample in this study consisted of 85 respondents. Data were collected through the distribution of questionnaires to respondents who met the research criteria. The data analysis technique used was PLS-SEM (Partial Least Squares Structural Equation Modeling) with the assistance of SmartPLS 3.0 software. The results of the study indicate that Work-Life Balance has a negative but insignificant effect on Burnout. Job Stress has a positive and significant effect on Burnout, while Workload has a positive but insignificant effect on Burnout. Regarding the Turnover Intention variable, Work-Life Balance shows a negative but insignificant effect. In addition, Job Stress and Workload also have positive but insignificant effects on Turnover Intention. Meanwhile, Burnout is proven to have a positive and significant effect on Turnover Intention. Furthermore, the results reveal that Burnout is unable to mediate the influence of Work-Life Balance and Workload on Turnover Intention because the indirect effects generated are insignificant. However, Burnout is able to positively and significantly mediate the influence of Job Stress on Turnover Intention.